2016
DOI: 10.2459/jcm.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged QT interval in ST-elevation myocardial infarction and mortality

Abstract: Hospital mortality was higher with prolonged QTc at prehospital-or-hospital admission, given equal Killip, TIMI and APACHE values. Discrimination of Killip, TIMI and APACHE values can be improved with prolonged QTc. Discrimination of a model including Killip, age and prolonged QTc is quite good. We have made a new simple prognostic scale with these variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
4
9
0
2
Order By: Relevance
“…It is possible that the prompt reperfusion therapy in our patients with STEMI will influence the temporal evolution of QTc intervals and the best measuring time of QTc intervals will thus be different. One recent study reported that prolonged QTc interval of first ECG (prehospital or hospital admission) predicted in-hospital mortality in patients with STEMI 22 , which is consistent with our findings. Our study is the first study to evaluate the effects of serial QTc interval changes on the long term outcomes in patients with STEMI exclusively receiving primary PCI.…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that the prompt reperfusion therapy in our patients with STEMI will influence the temporal evolution of QTc intervals and the best measuring time of QTc intervals will thus be different. One recent study reported that prolonged QTc interval of first ECG (prehospital or hospital admission) predicted in-hospital mortality in patients with STEMI 22 , which is consistent with our findings. Our study is the first study to evaluate the effects of serial QTc interval changes on the long term outcomes in patients with STEMI exclusively receiving primary PCI.…”
Section: Discussionsupporting
confidence: 92%
“…However, we have been able to confirm that, in a prognostic system using only 2 of the variables included in the previous study [30] (Killip and age), the discrimination is slightly inferior but continues to be a good discrimination (ROC area, 0.846) and that this is sufficient to be used in clinical practice. Furthermore, this new prognostic system is simpler and, therefore, easier to use, than the system, which includes QT interval and also easier to use than other systems habitually used, such as TIMI and GRACE [25][26][27].…”
Section: Discussionsupporting
confidence: 61%
“…Our group recently published a case-control study nested in a cohort [30], and as was stated in the introduction, the study centred on the evaluation of patients with prolonged QT interval and its prognostic implications in patients with AMI. The study also describes a new prognostic scale with 3 variables (Killip class, age, and prolonged QT), which has good discrimination (ROC area, 0.88).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, measures that can effectively hinder the damage associated with heart failure are important. AMI is the predominant cause of myocardial infarction, and left ventricular remodelling (LVM) occurs at a later stage (3). LVM refers to the pathological changes in the immune activation state of the body caused by large amounts of cytokines secreted by myocardial cells, under the influence of injury, ventricular wall stress, oxidative stress and partial activation of the neuroendocrine system, which induces myocardial collagen deposition and changes in collagen type and collagen degradation (4).…”
Section: Introductionmentioning
confidence: 99%